Analysis of the Influence of the Number of Torque Converter Blades on Working Performance Based on the Response Surface Method. Issue 2 (January 2021) - Xiong, Pan; Sun, Hongjun; Zhong, Jiping; Zhen, Chenping; Chen, Xinyuan; Gao, Huichao
Abstract: To understand the effect of the number of torque converter blades on the performance of torque converters, in this paper, we employed computational fluid dynamics and the response surface method to optimize the design of the torque converter. The number of pump blades, stator blades and turbine blades were used as design variables, and the torque transmission ratio and pump capacity factor were used as objective functions for multi-factor optimization design. The results show that the number of turbine blades had no significant impact on the converter's performance, while the number of pump blades and stator blades had significant impact and showed strong correlation. Compared with the original torque converter, the optimized converter increased the starting torque ratio by 0.12 and the efficiency by 4%. It shows that the computational fluid dynamics and the response surface method can be combined to determine the optimal number of blades in the design of torque converters to reduce the cost and experiment time.